Tangible Service Automation: Decomposing the Technology-Enabled Engagement Process (TEEP) for Augmented Reality. (February 2021) - Heller, Jonas; Chylinski, Mathew; de Ruyter, Ko; Keeling, Debbie I.; Hilken, Tim; Mahr, Dominik
The rise of augmented reality (AR) technology, which overlays digital content to alter customers' views of a physical service setting, using mobile and wearable computing, drives the digital automation of physical services. In particular, it promises to achieve tangibility even in service encounters delivered in digital formats. However, customer engagement with AR is falling short of expectations. Managers lack an integrated framework of AR service automation and therefore tend to focus on the technology rather than on the process of customer engagement with AR service automation. To address this problem, the current study proposes a technology-enabled engagement process that integrates multiple stages of customer engagement, as a service-centric process. To establish that engagement with AR service automation requires the inclusion of service tangibility, as part of the process, the authors decompose the steps of interactive service engagement, the spatial presence of the service, customers' emotional and cognitive engagement with the service, and perceived value-in-use, which lead to emergent behavioral forms of engagement.